Empréstimos do inglês na língua cabo-verdiana no presente e no passado - Jabłonka, Edyta (Studia Romanica Posnaniensia, 2023)
The main objective of the present study is to observe the influence of English on the Cape Verdean language, taking into account the historical events and the linguistic contacts between the languages in question. It is intended to observe how Anglicisms have been introduced in different contexts, especially in recent times, therefore, without forgetting the British and American influence in Cape Verde in past centuries and its impact on the lexicon. The semantic fields covered include, among others, new technologies, sports and music (rap kriol). The present descriptive research is based mainly on digital sources, such as social networks, online press, dictionaries available online and song texts. In conclusion, the analysis carried out proves the constant presence of Anglicisms in Cape Verdean reality, as well as their flow related to the emergence of new phenomena that need to be named.